Estudo de ciclo de vida de gerador eólico de pequeno porte utilizado em propriedade rural - Miranda, Amauri Ghellere Garcia (2018)
Technological advances seek to; somehow, improve the quality of life of the population. To ensure sustainability in new projects and methodologies are established. Among these methodologies to life cycle, assessment seeks to evaluate the energy cost and the environmental impact of a product. Thus, the present work had as purpose to carry out such analysis in a wind turbine installed in the project House, situation at the State University of Western Paraná UNIOESTE, Paraná, Brazil. The energy cost was checked following ISO 14040 and methodology the following methodology was verified energy return proposed by Manwell, 2010. This was exploratory research of bibliographic source. The weather data used to verify the energy return of the generator were actual data, provided by SIMEPAR. In this way, it was found that the energy cost of the material, used in the wind turbine, was 803 MJ. The environmental impact of wind turbine rated at this research, converted to CO2 equivalent, is 60 kgCO2. The capacity of power generation of the wind turbine, to weather conditions found at the scene of the analysis is of 1390 MJ/year when generating power at 12V current and 1278 MJ/year when at 24V.The analysis found that the energy embodied payback time of the wind turbine running at 12V is 11 months and 18 days and at 24V is 1 year and 18 days respectively.